1998
DOI: 10.1111/1467-8551.00101
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Conflict in the Franchise System

Abstract: This paper articulates the theoretical rationale for conflict in franchising, operationalizes conflict through the measurement of franchisee satisfaction and labels empirically supported stratified satisfaction levels. Two propositions are advanced in relation to the drivers of conflict in franchise systems. The first proposition is underpinned by relational exchange theory, which postulates that franchisee–franchisor goal congruence is important to the fulfilment of the alliance efficiencies which motivate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…They can achieve this goal in two ways: by developing trustful relationships [27][28][29] or by avoiding conflict with franchisees [7,[30][31][32]. To analyze how franchisors develop trustful relationships, studies have focused on measures of relationship quality [33], the franchisee's perceived relationship value [26], the moderators of the relationship [34], interpretation and perception asymmetries between franchisor and franchisee [35], the control mechanisms adopted to avoid free-riding and opportunistic behaviors [36], and the role of the wider business network [37].…”
Section: Economic Sustainability: Franchise Chain Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…They can achieve this goal in two ways: by developing trustful relationships [27][28][29] or by avoiding conflict with franchisees [7,[30][31][32]. To analyze how franchisors develop trustful relationships, studies have focused on measures of relationship quality [33], the franchisee's perceived relationship value [26], the moderators of the relationship [34], interpretation and perception asymmetries between franchisor and franchisee [35], the control mechanisms adopted to avoid free-riding and opportunistic behaviors [36], and the role of the wider business network [37].…”
Section: Economic Sustainability: Franchise Chain Survivalmentioning
confidence: 99%
“…To analyze how franchisors develop trustful relationships, studies have focused on measures of relationship quality [33], the franchisee's perceived relationship value [26], the moderators of the relationship [34], interpretation and perception asymmetries between franchisor and franchisee [35], the control mechanisms adopted to avoid free-riding and opportunistic behaviors [36], and the role of the wider business network [37]. To analyze how franchisors avoid conflict with franchisees, studies have focused on the influence of investments and the franchisor's support [7,30,31] and the effects of the allocation of decision rights [34]. Grunnhagen and Dorsch [34] found that the allocation of rights for decisions regarding local advertising, personnel, and merchandising-variety of products and store display-improve franchisor-franchisee relations.…”
Section: Economic Sustainability: Franchise Chain Survivalmentioning
confidence: 99%
“…However, this may be tricky because the two partners may disagree on certain provisions which, although pursuing homogeneity and preventing deviations, may also lead to serious conflict and eventual contract terminations. Actually, the very complexity of the franchise relationship makes conflict especially prevalent in this setting (Spinelli and Birley 1998;Winsor et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Spinelli and Birley's (1998) study among 421 U.S. franchisees demonstrated a positive correlation between franchisee satisfaction and goal alignment and adequate franchisor services. Studies on why franchisees leave the system have also linked poor communication to disruptive franchisee exits (Frazer & Winzar, 2005).…”
Section: The Franchisor-franchisee Relationshipmentioning
confidence: 90%
“…Franchising, therefore, requires a high need for coordination between the parties to ensure consistency for the consumer. Because franchisees are not employees who can be fired, and because the termination of a franchise contract is often a lengthy, timeconsuming process, franchisors must collaborate with franchisees to maximize their performance and profitability (Combs et aI., 2004;Spinelli & Birley, 1998). How the franchisor-franchisee relationship is both governed and nurtured has received significant attention by researchers over the last 30 years.…”
Section: The Franchisor-franchisee Relationshipmentioning
confidence: 99%